Embedded control of an inverter - Pua, Colin (2014)
This final year project was part of the Integrated Chemical and Electrical System Operation (ICESO) research development, headed by the Cambridge Centre for Carbon Reduction in Chemical Technology (C4T). The objective of this project was to develop a real-time Field-Programmable Gate Array (FPGA) algorithm for a controller board, which was capable of controlling a power inverter for electrical conversion operation. Making use of National Instruments‟ General Purpose Inverter Controller, this single-board RIO was armed with a FPGA Chip to utilize advantages such as true parallel processing. LabVIEW was chosen as the programming environment for its reliability and usability with the FPGA technology. This project required 2 parts of program codes; one in FPGA and another in Host Computer. In the FPGA algorithm, the program reads a 3-phase input voltages and converted this information for Sine-Triangle PWM Generation. Subsequently, these PWM signals were used as control signals to drive the inverter. At the same time, a Host Computer program was used to control the FPGA algorithm, perform signal analysis and display waveforms. One of the challenges faced was the data losses in some Direct Memory Access (DMA) First-In-First-Outs (FIFOs), which acted as data transfers between FPGA and Host Computer. Rectification was made to enhance the program codes. In addition, future similar projects could benefit from the recommendations and suggestions made.